2009
DOI: 10.1017/s1121189x00000312
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal affective disorder and latitude of living

Abstract: SUMMARYAim – Since the importance of latitude of living for the prevalence of Seasonal Affective Disorder (SAD) is unclear, the study aims to test the latitude hypothesis by comparing SAD in two rather similar groups of students living at latitudes far apart. Methods – Two groups of students, 199 in Tromsø, Norway (690 N) and 188 in Ferrara, Italy (440 N) were asked to fill in the Seasonal Pattern Assessment Questionnaire. Results – Global Seasonality score (GS-score) was significantly higher in Italian than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Regarding the lack of correlation between SPAQ scores and latitude in the present study, this finding agrees with other data from studies conducted in the southern hemisphere, such as in Australia 19 , but is opposite to studies conducted in the northern hemisphere [10][11][12][13] , which have shown significant correlations. This discrepancy between studies in southern and northern hemispheres gives rise to two possibilities: publication bias and magnitude of latitude range in the hemispheres.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the lack of correlation between SPAQ scores and latitude in the present study, this finding agrees with other data from studies conducted in the southern hemisphere, such as in Australia 19 , but is opposite to studies conducted in the northern hemisphere [10][11][12][13] , which have shown significant correlations. This discrepancy between studies in southern and northern hemispheres gives rise to two possibilities: publication bias and magnitude of latitude range in the hemispheres.…”
Section: Discussionsupporting
confidence: 88%
“…SAD has been attributed to lack of natural light in the winter at high latitudes, since a correlation between latitude and prevalence of SAD has been Seasonal Pattern Assessment Questionnaire in Brazil reported 10,11 . However, there are data in disagreement with this assumption 12,13 .…”
mentioning
confidence: 99%
“…Moreover, one would expect a higher prevalence of sufferers of SAD at higher latitudes [14,23,24]. There seems to be less correlation between prevalence rates of SAD and latitude than expected [25,26], and other factors like climate, genetic vulnerability and socio–cultural context may play a more important role [27]. Saarijarvi et al [28] found that the prevalence of overall and winter SAD did not differ between Finns living in northern and south-western Finland and that winter SAD was less frequent among the Sami.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial factors were also suggested to have an impact on seasonality [19,20]. Among geographic factors, latitude has been most widely studied, although recent studies consistently reported that it might have a minimal effect on the seasonality [17,21,22].…”
Section: Introductionmentioning
confidence: 99%